CXCL12/CXCR4 modulates macrophage efferocytosis to induce glomerular crescent formation and fibrosis via ELMO1/DOCK180/RAC1 signaling in ANCA-associated glomerulonephritis - Zilin Liu; Yongqi Deng; Xiaomei Song; Xin Cai; Huaying Xiong; Liwen Tan; Shengsen Wei; Qiulin Li; Xiong Wang; Wei Jiang; Yaxi Chen; Qiu Li; et al. (Cellular and Molecular Life Sciences)
Abstract Background ANCA-associated glomerulonephritis (AAGN) is a leading cause of uremia in children, driven by macrophages (Mφs) that mediate crescent formation and fibrosis. Despite their critical role, the signals governing monocyte recruitment and macrophage polarization in AAGN remain unclear. Methods We utilized single-cell sequencing to dissect the cellular dynamics of AAGN and conducted in vitro and in vivo experiments to explore the role of the CXCL12/CXCR4 signaling axis in monocyte recruitment and macrophage efferocytosis. Protein interaction analyses further delineated the downstream signaling pathways involved. Results CXCL12, released by apoptotic glomerular endothelial cells, recruited CXCR4+ monocytes to renal tissue, where they differentiated into M2-polarized macrophages and contributed to the progression of AAGN. CXCR4 signaling mediated M2 polarization via the ELMO1/DOCK180/ RAC1 efferocytosis pathway, resulting in the secretion of TGF-β1 to promote the progression of the crescent to fibrosis. Plasma CXCL12 and CXCR4 levels, along with CXCR4+ macrophage infiltration, distinguished AAGN from other crescentic nephritis types. LIT927 and AMD3100 treatment significantly alleviated renal dysfunction and crescent formation in EAV models. Conclusions This study revealed that CXCL12/CXCR4 signaling axis plays a key regulatory role in the pathological process of AAGN. By establishing the specific molecular dialogue mechanism between endothelial cells and monocytes/macrophages, CXCL12 released by apoptotic endothelial cells can activate the CXCR4 on the surface of monocytes/macrophages, thereby promoting monocyte migration, enhancing macrophage-mediated efferocytosis and transforming into a pro-fibrotic phenotype. Targeted intervention with CXCL12/CXCR4 provides a promising approach for the treatment of AAGN. Graphical abstract In MPO + AAGN, apoptotic renal endothelial cells release the "find me" signal CXCL12, attracting CXCR4⁺CD163⁺ monocytes from peripheral blood, which differentiate into AAGN-specific Mφs. CXCR4 on these renal tissue-specific macrophages interacts with ELMO1, activating the ELMO1/DOCK180/RAC1 efferocytosis signaling axis to drive Mφ polarization toward the M2 phenotype. This polarization fosters glomerular sclerosis and a fibrotic microenvironment characterized by high TGF-β1 expression, accelerating the fibrotic progression of AAGN